Pengaruh Pengetahuan dan Modal Minimal Terhadap Minat Investasi Mahasiswa UIN Ar-Raniry - Iskandar, Evy; Vonna, Rizki Dara (Fakultas Ekonomi dan Bisnis Islam, Universitas Islam Negeri Ar-Raniry Banda Aceh, 2023)
Access to the Islamic Capital Market makes it easier for all people, including students, to invest in Islamic stocks. This study aims to analyze the effect of investment knowledge and minimum capital variables toward the intention at student of Economics and Islamic Business Faculty (FEBI) - Ar Raniry State Islamic Univesity in investing on the Islamic Capital Market Islamic. This study uses a quantitative approach by multiple linear regression analysis, and it processed proportionate stratified random sampling with data sourced from questionnaires of 96 students as samples. The results of the study show that: Partially, investment knowledge has no effect on investment intentions, in contrast to minimal capital, which has an effect on student investment intentions. Meanwhile, simultaneously it shows that the two independent variables have effected on students' intention in investing in the Islamic Capital Market.